The Evolution of Clinicopathological Diagnostic Features of Upper Tract Urothelial Carcinoma in China: A Summary of 2561 Cases in the Last 20 Years - Xu, Chunru; Yuan, Changwei; Zhang, Cuijian; Fang, Dong; Yu, Yanfei; Wang, Xiang; Li, Zhihua; Wang, Yan; Tang, Qi; Xiong, Gengyan; Zhang, Lei; He, Zhisong; et al. (Frontiers in Oncology, 2022)
Objectives: To summarize the clinicopathological diagnostic features and evolutionary trends of upper tract urothelial carcinoma (UTUC) in China over the past 20 years. Methods: All patients diagnosed with upper tract urothelial carcinoma in the Peking University First Hospital from 2001 to 2020 were retrospectively collected. Data were divided into two groups (2001-2010 and 2011-2020) according to the date of diagnosis. Statistical analysis was done with the SPSS V22.0. Chi-square analysis and t-test were adopted to analyze depending on the data type. Subgroup analysis based on 5 years was used for visualization to present trends. Both Kaplan-Meier curve and Cox regression were used for univariate and multivariate survival analysis. Results: The study included 2561 cases diagnosed with upper tract urothelial carcinoma in total. Compared with the first decade (2001-2010), patients of the second decades (2011-2020) had elder mean age (66.65 versus 67.59, years, p=0.025), higher male proportion (43.5% versus 49.0%, p=0.034), lower incidence of renal pelvic tumors (53.4% versus 45.8%, p＜0.001) and multifocality (18.6% versus 12.0%, p＜0.001), higher incidence of ureteral tumors (52.2% versus 60.9%, p＜0.001).In recent ten years, the incidence of muscle-invasive urothelial carcinoma (pT2+) decreased significantly (64.4% versus 54.9%, p＜0.001),and the mean size of renal pelvic tumors increased(3.46 versus 3.73, cm, p=0.043). The size of the ureteral tumor, the histopathologic grade showed no significant change. The prognostic analysis based on 709 patients regularly followed at our center revealed that the male gender and G3 histopathological grade were independent risk factors for poorer prognosis in patients with UTUC. Conclusion: In the past 20 years, the clinicopathological diagnostic features of upper tract urothelial carcinoma in the Chinese population has changed significantly, suggesting an increased risk of a poorer prognosis for UTUC. This trend may be related to updating diagnostic techniques and self-monitoring awareness. However, we need more high-grade, multicenter trials to verify it in the future.